Augusto Del Noce and the problem of totalitarianism - Berti, Francesco (Wydawnictwo Uniwersytetu Wrocławskiego, 2018)
The aim of this paper is to present the refl ections of the Italian philosopher Augusto Del Noce 1910–1989 on totalitarianism and highlight some of the problems that this perspective can lead to in the analysis of the totalitarian phenomenon. Del Noce originally developed a philosophical and transpolitical interpretation of modernity, secularization and totalitarianism, pre-empting, in the early 1960s many of the arguments developed later by “revisionist” scholars: Fascism was an imperfect form of totalitarianism; Nazism was a reaction to Communism; Communism was the most perfect example of the totalitarian State. The philosophical reconstruction of Del Noce is focused on the dichotomy between theism and atheism. Modernity is identifi ed tout court with the rationalist rejection of the concept of original sin, from which atheism and totalitarianism necessarily follow, the latter being as an essential and necessary moment in the process of atheization of society. The assumption on which this interpretation is founded, however, is questionable, in that it is reductive.
Keywords: Del Noce Augusto; totalitaryzm; nowoczesność; wolność; Gentile Giovanni; Gramsci Antonio